The debt threat : the dangers of high real interest rates for the world economy - Congdon, Tim. (Oxford, UK ; New York, NY, USA : B. Blackwell, 1988)
The book seek to highlight a problem of disintegration of the international financial system, the imminent breakdown of Western civilization and its challenges like the explosive growth of debt in both developed and developing countries.
Includes index.
Bibliography: p. [231]-238.
usc 19/10/18
Loans
Keywords: Debt; Interest rates